Edukasi Pembuatan MP-ASI Bahan Dasar Pangan Lokal 2 Hewani 1 Nabati sebagai Upaya Percepatan Penurunan Stunting Kabupaten Kendal - Candra Mustikaningrum, Ardian; Nafillah, Nafillah; Puspita Sari, Amanda (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
Toddlers are a group vulnerable to various nutritional problems caused by changes in physiological function. One of the nutritional problems that occurs is stunting. The prevalence of stunting in Kendal Regency in 2023 will reach 11.4%. The cause of this problem is the mother's nutritional parenting patterns and inappropriate fulfillment of nutritional needs for toddlers. In fact, Kendal Regency is a coastal area that has the potential for abundant fish as a source of animal protein. This fish can be used as a basic ingredient for making complementary foods for breast milk (MP-ASI) for stunted children. Providing this complementary food can be done by modifying processed products in the form of catfish and shrimp as animal protein with the addition of tofu as a source of vegetable protein. This preparation can be made into a dragon's foot product which is one of toddlers' favorite foods. This community service aims to provide education to mothers of toddlers so they can make MP ASI independently using local basic ingredients. The methods in this activity are opening, presentation of material, demonstration of making MP ASI from local food ingredients 2 animal 1 vegetable, discussion and evaluation. A total of 37 participants took part in this activity, who had filled out a questionnaire. The results show that there has been an increase in knowledge of making MP ASI using local food ingredients.